Treatment of water from wells for the supply of small communities: treatment of water from wells - Caldera, Yaxcelys; Rincón, Eudardo; González, Yoalis; Gutiérrez, Edixon (Impacto Científico, 2022)
The objective of this research was to analyze the methods of treating water from wells for the supply of small communities. The research was descriptive, with a field design. Eighteen houses with private wells in the state of Zulia (Venezuela) were visited, and information was collected through a survey of the owners, inquiring about the quality, use and treatment of well water. The results showed that the waters of the wells do not receive treatment and are perceived as brackish, with a cloudy appearance and yellow coloration. The water is used in food preparation, personal hygiene, home hygiene, laundry, irrigation and consumption. Among the treatment alternatives were: disinfection, aeration, softening, sedimentation, reverse osmosis, filtration, and removal of arsenic. It is recommended to carry out the physicochemical and microbiological characterization of the waters to select a treatment method or system that allows improving its quality.